Impact of school facilities on working behavior of teachers - Leung, Mei‐yung; Chan, John K.W.; Wang, Zhaohong (International Journal of Strategic Property Management, 2010)
From 1998–99 to 2003–04, the Hong Kong government increased investment in education by 20%. A number of primary schools have been rehoused in new millennium school buildings that have innovative facilities as well as a new design quite different from the design of traditional school buildings. However, whether the money was spent appropriately and cost‐effectively as a way of improving education in Hong Kong remains a debatable point. To investigate the facilities management (FM) of new millennium primary schools, a study was conducted of teachers who had worked in old traditional school buildings and then moved to new millennium school buildings. Since staff rooms are the major working areas for teachers, the study focused on the levels of satisfaction with the performance of FM in the staff rooms of primary schools and on the working behavior of primary teachers. Two questionnaire surveys were conducted of 113 teachers who had worked in both types of school buildings. Independent‐sample T‐tests were employed to evaluate the quantitative data that was collected from the teachers at the two stages in order to investigate the enhancement of FM in millennium school staff rooms and its impact on the working behavior of teachers. The results showed that FM in the staff rooms of the new millennium schools in Hong Kong was remarkably different from FM in the old schools. However, the teachers did not consider that their working behavior were significantly better in the millennium schools. The governmental investment is considered a success to a certain extent, but there are still a lot of areas where construction professionals and facilities managers of primary schools should improve millennium primary school projects in order to achieve the requirements of end‐users. First Published Online: 18 Oct 2010